The evolution of gender gaps in industrialized countries - Claudia Olivetti; Barbara Petrongolo (Queen Mary University of London, School of Economics and Finance, 2016)
Women in developed economies have made major inroads in labor markets throughout the past century, but remaining gender differences in pay and employment seem remarkably persistent. This paper documents long-run trends in female employment, working hours and relative wages for a wide cross-section of developed economies. It reviews existing work on the factors driving gender convergence, and novel perspectives on remaining gender gaps. The paper finally emphasizes the interplay between gender trends and the evolution of the industry structure. Based on a shift-share decomposition, it shows that the growth in the service share can explain at least half of the overall variation in female hours, both over time and across countries.
Keywords: E24; J16; J31; 330; Gender gaps; Demand and supply; Industry structure; Weibliche Arbeitskräfte; Arbeitszeit; Fraueneinkommen; Arbeitsmarktdiskriminierung; Industriestruktur; Shift-Share-Analyse; Industrieländer